Complications in Pediatric Regional Anesthesia: An Analysis of More than 100, 000 Blocks from the Pediatric Regional Anesthesia Network. (October 2018) - Walker, Benjamin J.; Long, Justin B.; Sathyamoorthy, Madhankumar; Birstler, Jennifer; Wolf, Christine; Bosenberg, Adrian T.; Flack, Sean H.; Krane, Elliot J.; Sethna, Navil F.; Suresh, Santhanam; Taenzer, Andreas H.; Polaner, David M.; et al.
Editor's Perspective: What We Already Know about This Topic: Regional anesthesia is associated with a low but poorly quantified incidence of complications. What This Article Tells Us That Is New: In a prospective multicenter cohort of more than 100, 000 blocks in children, there were no cases of permanent neurologic deficit associated with regional anesthesia. The rate of transient neurologic deficit was low at 2.4 per 10, 000, and the incidence of local anesthesia toxicity was also low at 0.76 per 10, 000. Background: Complications in pediatric regional anesthesia are rare, so a large sample size is necessary to quantify risk. The Pediatric Regional Anesthesia Network contains data on more than 100, 000 blocks administered at more than 20 children's hospitals. This study analyzed the risk of major complications associated with regional anesthesia in children. Methods: This is a prospective, observational study of routine clinical practice. Data were collected on every regional block placed by an anesthesiologist at participating institutions and were uploaded to a secure database. The data were audited at multiple points for accuracy. Results: There were no permanent neurologic deficits reported (95% CI, 0 to 0.4:10, 000). The risk of transient neurologic deficit was 2.4:10, 000 (95% CI, 1.6 to 3.6:10, 000) and was not different between peripheral and neuraxial blocks. The risk of severe local anesthetic systemic toxicity was 0.76:10, 000 (95% CI, 0.3 to 1.6:10, 000); the majority of cases occurred in infants. There was one epidural abscess reported (0.76:10, 000, 95% CI, 0 to 4.8:10, 000). The incidence of cutaneous infections was 0.5% (53:10, 000, 95% CI, 43 to 64:10, 000). There were no hematomas associated with neuraxial catheters (95% CI, 0 to 3.5:10, 000), but one epidural hematoma occurred with a paravertebral catheter. No additional risk was observed with placing blocks under general anesthesia. The most common adverse events were benign catheter-related failures (4%). Conclusions: The data from this study demonstrate a level of safety in pediatric regional anesthesia that is comparable to adult practice and confirms the safety of placing blocks under general anesthesia in children. Abstract : In a prospective multicenter cohort of more than 100, 000 blocks in children, there were no cases of permanent neurologic deficit associated with regional anesthesia. The rate of transient neurologic deficit was low at 2.4 per 10, 000, and the incidence of local anesthesia toxicity was also low at 0.76 per 10, 000.